2019
DOI: 10.3390/jmse7060164
|View full text |Cite
|
Sign up to set email alerts
|

Growth Aspects and Biochemical Composition of Synechococcus sp. MK568070 Cultured in Oil Refinery Wastewater

Abstract: The aim of the study was to explore the possibility of bioremediation of oil refinery wastewaters by the cyanobacterium Synechococcus sp. MK568070, isolated from the Adriatic Sea. The potential of biomass and lipid production was explored upon cultivation on oil refinery wastewater with excess CO2 after the removal of nutrients. The strain grew well in a wide range of salinities and ammonium concentrations, and was further tested on the wastewater from local oil refinery plant of various N-composition. Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The experiments presented herein represent growth on wide range of NH 4 + , however under constant high salinity (38 psu) corresponding to Northern Adriatic. Previous research [72] demonstrated wide salinity tolerance of Synechococcus sp. MK568070.…”
Section: Phormidium Lucidum Mk568072mentioning
confidence: 97%
“…The experiments presented herein represent growth on wide range of NH 4 + , however under constant high salinity (38 psu) corresponding to Northern Adriatic. Previous research [72] demonstrated wide salinity tolerance of Synechococcus sp. MK568070.…”
Section: Phormidium Lucidum Mk568072mentioning
confidence: 97%
“…Confidence intervals for biomass FIGURE 1 A scheme of 4 photobioreactors (PBR). Temperature, air/CO 2 bubbling, pH, light intensity and diurnal cycle are controlled by SCADA system (Blazǐna et al, 2019).…”
Section: Growth Analysis and Estimation Of Kinetic Parametersmentioning
confidence: 99%
“…In addition to the high concentrations of ammonium, ORWW contains high concentrations of organic, and inorganic pollutants, such as petroleum hydrocarbons, mercaptans, polycyclic aromatic hydrocarbons (PAHs), benzene homologues, crude oil, heavy metals etc. (Jiang et al, 2010;Blazǐna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%